2015
DOI: 10.5194/bg-12-3321-2015
|View full text |Cite
|
Sign up to set email alerts
|

WETCHIMP-WSL: intercomparison of wetland methane emissions models over West Siberia

Abstract: Abstract. Wetlands are the world's largest natural source of methane, a powerful greenhouse gas. The strong sensitivity of methane emissions to environmental factors such as soil temperature and moisture has led to concerns about potential positive feedbacks to climate change. This risk is particularly relevant at high latitudes, which have experienced pronounced warming and where thawing permafrost could potentially liberate large amounts of labile carbon over the next 100 years. However, global models disagr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(143 citation statements)
references
References 110 publications
(168 reference statements)
4
129
1
Order By: Relevance
“…Interestingly, the situation is different for Russia where top-down and bottomup approaches show similar mean emissions from natural wetlands (mostly boreal, ∼ 13-14 Tg CH 4 yr −1 ), consistently with Kaplan (2002) but not with Matthews and Fung (1987), who infer almost 50 Tg CH 4 yr −1 for Russia. Wetland emissions from Russia appear very uncertain, as also found by Bohn et al (2015) for western Siberia. Wetland emissions from tropical South America are found more consistent in this work than in Kirschke et al (2013), where topdown inversions showed 2 times less emission than bottomup models.…”
Section: Regional Methane Emissions Per Source Categorymentioning
confidence: 58%
See 3 more Smart Citations
“…Interestingly, the situation is different for Russia where top-down and bottomup approaches show similar mean emissions from natural wetlands (mostly boreal, ∼ 13-14 Tg CH 4 yr −1 ), consistently with Kaplan (2002) but not with Matthews and Fung (1987), who infer almost 50 Tg CH 4 yr −1 for Russia. Wetland emissions from Russia appear very uncertain, as also found by Bohn et al (2015) for western Siberia. Wetland emissions from tropical South America are found more consistent in this work than in Kirschke et al (2013), where topdown inversions showed 2 times less emission than bottomup models.…”
Section: Regional Methane Emissions Per Source Categorymentioning
confidence: 58%
“…In these models, methane emissions from wetlands to the atmosphere are computed as the product of an emission density (which can be negative; mass per unit area and unit time) multiplied by a wetland extent (see the model intercomparison studies by Melton et al, 2013, andBohn et al, 2015). The CH 4 emission density is represented in land surface models with varying levels of complexity.…”
Section: Wetlandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wetland maps generated using these different approaches show substantial differences. Remote sensing data sets estimate relatively high levels of inundation in regions of Canada that are not forested or have many small lakes (see further discussion in Melton et al, 2013;Bohn et al, 2015). By contrast, modeling approaches that dynamically generate wetland area or use land cover maps assign more wetlands over regions with high water tables but little surface water as seen by remote sensing based inundation data sets.…”
Section: Spatial Distribution Of the Fluxesmentioning
confidence: 99%